Pengaruh obesitas pada kualitas tidur mahasiswa Fakultas Kedokteran Universitas Udayana periode 2018 - Yudha Anggoro Kawi; Desak Made Wihandani; I Wayan Surudarma (DiscoverSys Inc., 2019)
Introduction: Increased obesity rates in adolescents can lead to the emergence of new risk populations for the occurrence of sleep disorders. The emergence of sleep disorders will have a direct impact on decreasing the quality of sleep. This study aims to determine the effect of obesity on the sleep quality of students of the Faculty of Medicine, Udayana University.Method: The study design was cross sectional analytic with a total sample of 74 students of the Medical Faculty of Udayana University (37 samples of the Body Mass Index (BMI) obesity and 37 samples of the normal BMI). Sample selection is done randomly. Measuring sleep quality was done through filling in the Pittsburgh Sleep Quality Index (PSQI) questionnaire and measuring obesity was done by calculating BMI. The answers to the questionnaire were scoring and based on the global score, sleep quality was categorized into poor and good sleep quality. The PSQI questionnaire also included questions about health problems experienced by students in the past month. Data analysis is presented in the form of tables and narratives.Result: The results showed that in the obese student group there were 22 samples with poor sleep quality (53.7%) and 15 samples with good sleep quality (45.5%). In the normal IMT student group there were 19 samples with poor sleep quality (46.3%) and 18 samples with good sleep quality (54.5%). In 20 students with health problems, there were 15 samples with poor sleep quality and 5 samples with good sleep quality. In 54 students without health problems, 26 samples with poor sleep quality and 28 samples with good sleep quality. Analysis using chi-square showed obesity did not have a significant effect on sleep quality (p = 0.483). There was a significant effect of health problems on sleep quality (p = 0.039).Conclusion: Conclusions of the study were obesity did not have a significant effect on the quality of sleep of students of the Faculty of Medicine, Udayana University.